Penyuluhan Pemasaran Pasca Pandemi Covid-19 di Kawasan Wisata Pantai Cemara - Lalu Adi Permadi; GA Sri Oktariyani; Nur Aida Arifah Tara; Diswandi Diswandi (Universitas Mataram, 2022)
Cemara Beach which is located in South Sheet Village, Lembar District, West Lombok Regency is a potential tourist location to be developed. To redevelop the Cemara Beach Area as a post-Covid-19 tourist location, a good marketing strategy is needed. The Mataram University Community Service activity carried out in the Cemara Beach area aims to provide marketing knowledge to tourism actors in order to prepare the right marketing strategy after the Covid-19 Pandemic. This activity was carried out by means of door-to-door lectures along the beach in Cemara Hamlet. This is because this service took place at a time when the Pandemic was still ongoing. The result of this activity is that tourism actors at Cemara Beach are able to develop tourism marketing strategies that can be applied after the Covid-19 pandemic. Of all the service activities in Cemara Hamlet, this community service activity succeeded in providing enlightenment about marketing science to tourism actors about the Marketing Strategy that will be carried out after Covid-19.